STAT4 Gene Polymorphisms Are Associated with Susceptibility and ANA Status in Primary Biliary Cirrhosis. (4th February 2014) - Joshita, Satoru; Umemura, Takeji; Nakamura, Minoru; Katsuyama, Yoshihiko; Shibata, Soichiro; Kimura, Takefumi; Morita, Susumu; Komatsu, Michiharu; Matsumoto, Akihiro; Yoshizawa, Kaname; Ishibashi, Hiromi; Tanaka, Eiji; et al.
Abstract : Recent genome-wide association studies suggest that genetic factors contribute to primary biliary cirrhosis (PBC) susceptibility. Although several reports have demonstrated that the interleukin (IL) 12 signaling pathway is involved in PBC pathogenesis, its precise genetic factors have not been fully clarified. Here, we performed an association analysis between IL12A, IL12RB, and signal transducer and activator of transcription 4 (STAT4) genetic variations and susceptibility to PBC. Single nucleotide polymorphisms (SNPs) were genotyped in 395 PBC patients and 458 healthy subjects of Japanese ethnicity and evaluated for associations with PBC susceptibility, anti-nuclear antibody (ANA) status, and anti-mitochondrial antibody (AMA) status. We detected significant associations with PBC susceptibility for several STAT4 SNPs (rs10168266; P = 9.4 × 10 - 3, rs11889341; P = 1.2 × 10 - 3, rs7574865; P = 4.0 × 10 - 4, rs8179673; P = 2.0 × 10 - 4, and rs10181656; P = 4.2 × 10 - 5 ). Three risk alleles (rs7574865; P = 0.040, rs8179673; P = 0.032, and rs10181656; P = 0.031 ) were associated with ANA status, but not with AMA positivity. Our findings confirm that STAT4 is involved in PBC susceptibility and may play a role in ANA status in the Japanese population.